A follow-up study of the use of DIAGNOdent for monitoring fissure caries in children - Anttonen V, Seppa¨ L, Hausen H. (Blackwell Synergy, 2004)
The aim of this study was to evaluate the utility of the laser fluorescence device DIAGNOdent for monitoring occlusal caries longitudinally as part of a routine dental check-up in a public dental clinic.